Incidence and Risk Factors for Renal Dysfunction in HIV Patients Anti-Retroviral Therapy-Naïve that accepts TLD at Prof. Dr. dr. IGNG Ngoerah Hospital: A Prospective Cohort Study - Duarsa, Made Dyah Vismita Indramila; Somia, I Ketut Agus (Institute of Topical Disease Universitas Airlangga, 2025)
The administration of TLD in ART-naive HIV patients can reduce kidney function, with certain risk factors potentially exacerbating side effects. This study investigates the incidence of kidney dysfunction and associated risk factors among ART-naive HIV patients initiating treatment with TLD. A prospective cohort study was conducted at Prof. Dr. dr. IGNG Ngoerah Hospital. The study population comprised HIV-1-infected, ART-naive adults selected through simple random sampling. Data were collected between July and August 2024, with a two-week follow-up after the initial ART dose. SPSS version 25 was used for data analysis, including chi-square, paired-sample t-tests, and logistic regression tests. A p-value of ≤0.05 was considered significant. Among 52 patients (18 women, 34 men; mean age 40.29±11.23 years), 13 (25%) experienced kidney dysfunction before ART, increasing to 24 (46.2%) two weeks after treatment. GFR changes were insignificant (100.48±22.999 vs. 96.303 ± 23.059, p-value=0.1). However, age at diagnosis and anemia are found to be significant as risk factors for kidney dysfunction in bivariate analysis (RR = 6.071, 95%CI 1.823-20.217, p-value=0.002; RR = 3.091, 95%CI 0.990-9.647, respectively). Based on multivariate analysis, the age of diagnosis is an independent risk factor of kidney dysfunction (adjusted RR = 6.071, 95%CI 1.823-20.217, p-value=0.003). Other factors, including gender, BMI, hypertension, diabetes, and hepatitis, were insignificant (p-value>0.05). Age at diagnosis emerged as an independent risk factor for renal dysfunction in ART-naive individuals starting TLD.